2011
DOI: 10.1051/0004-6361/201015939
|View full text |Cite
|
Sign up to set email alerts
|

The globular cluster systems of Abell 1185

Abstract: We examine the properties of a previously discovered population of globular clusters in the heart of the rich galaxy cluster Abell 1185 that might be intergalactic in nature. Deep images obtained with the Advanced Camera for Surveys (ACS) aboard Hubble Space Telescope (HST) confirm the presence of ∼1300 globular clusters brighter than I F814W 27.3 mag in a field devoid of any large galaxies. The luminosities and colors of these objects are found to be similar to those of metal-poor globular clusters observed i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 84 publications
2
28
0
Order By: Relevance
“…Those authors estimated that about 30% to 40% of globular clusters in Coma are intra-cluster globular clusters. West et al (2011) confirmed the presence of ∼ 1300 globular clusters in the Abell 1185 galaxy cluster that apparently are not bound to any galaxy. Recently, Harris and Mulholland (2017) estimate ∼ 50000 − 80000 intra-cluster globular clusters in the Perseus cluster, with a radial distribution extending several kiloparsecs away from the cluster center.…”
Section: Introductionsupporting
confidence: 53%
“…Those authors estimated that about 30% to 40% of globular clusters in Coma are intra-cluster globular clusters. West et al (2011) confirmed the presence of ∼ 1300 globular clusters in the Abell 1185 galaxy cluster that apparently are not bound to any galaxy. Recently, Harris and Mulholland (2017) estimate ∼ 50000 − 80000 intra-cluster globular clusters in the Perseus cluster, with a radial distribution extending several kiloparsecs away from the cluster center.…”
Section: Introductionsupporting
confidence: 53%
“…(e.g., West et al 2011). Although GCs have been found distributed between galaxies in rich clusters (e.g., Peng et al 2011;West et al 2011), their density drops with clustercentric radius, and we would not expect a significant number of IC GCs at the location of this SN Ia, 616 kpc from the BCG.…”
Section: Abell 399mentioning
confidence: 86%
“…The first posits that globular clusters are formed in galaxies, but that strong galaxy-galaxy interactions might subsequently lead to some fraction becoming unbound. This is thought to be the origin of the significant IGC populations observed in galaxy clusters, where close encounters between galaxies frequently lead to tidal disruption or stripping (e.g., West et al 2011; ⋆ E-mail: dougal.mackey@anu.edu.au Samsing 2015). It is well known that galaxy interactions, mergers and accretions have occurred in the Local Group.…”
Section: Introductionmentioning
confidence: 99%